Hypothalamic-pituitary-adrenocortical dysfunction in elderly, male marathon runners: feedback sensitivity, stress response, and effects on verbal memory - Deuschle, Michael (Neuroendocrinology, 2017)
Animal studies suggest that repeated episodes of elevated glucocorticoids lead to a dysregulation of the hypothalamic-pituitary-adrenal (HPA) system at a suprapituitary level, and to impaired mnemonic function. We compared cognitive tests, as well as feedback integrity and stress responsivity of the HPA system, between 11 elderly, male marathon runners - a model of repeated HPA system activation - and 10 sedentary controls. The marathon runners had significantly increased baseline, stress, and post-stress ACTH - but not cortisol - concentrations. Also, suppression of ACTH by 3 mg dexamethasone was impaired in the athletes compared to the control subjects, while the ACTH and cortisol response to additional CRH did not differ between the 2 groups. Finally, long-term verbal memory was impaired in the athletes compared to the controls. Regarding the HPA system, these findings are in accordance with an acquired suprapituitary feedback disturbance in marathon runners; however, the similar glucocorticoid concentrations in the 2 groups may be due to reduced adrenal sensitivity to ACTH. Together with impaired verbal memory, these data support the assumption that repeated episodes of HPA system activity may exert negative effects at the level of the hippocampus.